Comparison between overlay and underlay primary myringoplasty: retrospective analysis on anatomical and functional results in 497 adult patients - Ricciardiello, Filippo; Pisani, Davide; Petruzzi, Gerardo; Viola, Pasquale; Palladino, Remo; Sequino, Giulio; Raucci, Aldo Falco; Motta, Giovanni; Coppola, Ciro; Cavaliere, Michele; Astorina, Alessia; Di Nola, Claudio; et al. (Acta Biomedica Atenei Parmensis, 2022)
Purpose: Retro-auricular approach using an autologous graft is the main surgical method for myringoplasty (MPL). Endaural and transcanal or endoscopic approaches are also used. There is no definitive consensus on the best MPL surgical technique. The aim of this study is to compare the two most used technique, over and underlay MPL, to evaluate the difference in anatomical and functional outcomes. Materials and methods: We made a retrospective analysis of 497 adult patients who underwent underlay or overlay primary MPL, between 2010 and 2018, and evaluated the difference in anatomical and functional outcomes. Results: Successful functional results, evaluated 18 months after surgery, were obtained in 380 patients (76,4%); the underlay MPL obtained a successful result in 85% of patients, while the overlay technique in the 68%. We observed anatomical failure in 13.4% patients, in detail 9,8% of underlay MPL and 17,2% of overlay MPL had an anatomical failure. Conclusion: Our results show less complications related to the underlay technique. We believe that this remains the technique to prefer, except in subtotal or wide anterior perforations that could be better managed using the overlay technique.